Public administration of agricultural lands through the development of a state land policy strategy - Rybalko , Kostyantyn (Pressing Problems of Public Administration, 2024)
This article addresses the theoretical aspects of public administration of agricultural lands, with a focus on incorporating strategic vision into land resource management through the development of a state land policy strategy. The aim of the article is to theoretically substantiate the “framework” of a new concept for Ukraine’s state land policy strategy, based on a functional analysis of the public governance aspects within the land sector. This encompasses goals, plans, programs, strategies, and concepts, covering various directions of land policy. It is highlighted that agricultural lands constitute a significant portion of the country’s total land area and have suffered the most severe negative impacts from the full-scale war, including removal from circulation due to occupation, landmines, and contamination. The article emphasises that strategic governance in public administration is not a new process in state policy development, as it is regulated by the existing legal framework, and strategic state governance is already underway at the national level. The article concludes that, in the current context of ongoing martial law and considering the prospects of post-war recovery, there is no comprehensive strategic vision for a unified state land policy. Such a vision is essential to provide a systematic and objective understanding of the current state of Ukraine’s land resources, outline existing problems, set the goals and principles of state land policy, identify its strategic objectives, implementation stages, and include critical components such as monitoring and anticipated outcomes. It is recommended to develop a state land policy strategy, with a detailed structure comprising specific components (sections). This strategy should become a comprehensive document that integrates the various fragmented aspects of land policy currently scattered across numerous existing documents — goals, plans, programs, strategies, and concepts. Furthermore, it should serve as a pragmatic response to societal demands for effective tools to address pressing issues in land relations.